Analytical Data Representation - Mishra, Sandip (International Journal of Computer Sciences and Engineering, 2019)
Electricity, gas and water are the basic needs of our life. We cannot imagine our life without these resources. To sustain our lives and make our household living easier, we depend on these different resources. The household living can only get better if we’re able to utilize the resources efficiently and in a sustained manner. Analytical Data Representation helps to study the data related to different events to help and analyze various related activities to aid in several purpose. The idea of Analytical Data Representation in this project is to track and keep the record of consumption of various resources like water, gas, electricity and others of a building of a certain area. It is highly recommended and required for modern lifestyle as it reduces the time to retrieve the information and details of resource consumption easily. Calculating the resource consumption details of a building manually requires more time and effort and if the consumption target is to be set or consumption details of previous year or month has to be viewed, it’s another hard work. This tiresome work can be automated using the concept of Analytical Data Representation.